mitología convertida en literatura juvenil: lecturas e imágenes del héroe Perseo en el siglo XXI - García Manso, Angélica (Huarte de San Juan. Filología y Didáctica de la Lengua, 2021)
Our study deals with the treatment of the myth of the hero Perseus in the Children’s Literature published in Spain in the 21st century. The analysis offers the clues that characterize the readings of Christian Grenier, Geraldine McCaughrean, Lucy Coats, Ana María Shua and Maria Angelidou. The updating of the myth is based on proposals such as, among others, political sociology, hybridization with other myths, association with modern fantasy, daily perception of the extraordinary, the literary or aesthetic recreation, versions into tweets, etc. All these keys underlie the texts and justify them pedagogically.